Presence of Virulence Genes in Enterococcus Species Isolated from Meat Turkeys in Germany Does Not Correlate with Chicken Embryo Lethality. (30th October 2019) - Maasjost, Julia; Lüschow, Dörte; Kleine, Anne; Hafez, Hafez M.; Mühldorfer, Kristin
Abstract : Virulence-associated traits have frequently been studied in enterococci and are considered to contribute towards the pathogenicity of infections. In the present study, Enterococcus isolates were collected during diagnostic investigations from meat turkeys in Germany. Twenty-eight isolates of three different Enterococcus species were analyzed for five selected putative virulence traits to understand their potential role in the pathogenicity using the chicken embryo lethality assay. Ten E. faecalis, ten E. faecium, and eight E. gallinarum isolates were examined for the presence of common virulence genes and their phenotypic expression, namely, the cytolysin operon, five individual cyl genes ( cylL L, cylL S, cylM, cylB, and cylA ), gelatinase ( gelE ), hyaluronidase ( hyl Efm ), aggregation substance ( asa1 ), and enterococcal surface protein ( esp ). The Enterococcus isolates showed significant species-dependent differences in the presence of genotypic traits (p < 0.001 by Fisher's exact test; Cramer's V  = 0.68). At least one gene and up to three virulence traits were found in E. faecalis, while six E. faecium isolates and one E. gallinarum isolate did not display any virulence-associated pheno- or genotype. More than half of the Enterococcus isolates ( n  = 15) harbored the gelE gene, but only E. faecalis ( n  = 10) expressed the gelatinase activity in vitro . The hyl Efm gene was found in five E. gallinarum isolates only, while seven isolates showed the hyaluronidase activity in the phenotypic assay. In Cramer's V statistic, a moderate association was indicated for species ( V  ≤ 0.35) or genotype ( V  < 0.43) and the results from the embryo lethality assay, but the differences were not significant. All E. gallinarum isolates were less virulent with mortality rates ranging between 0 and 30%. Two E. faecalis isolates were highly virulent, harboring the whole cyl -operon as well as gelE and asa1 genes. Likewise, one E. faecium isolate caused high embryo mortality but did not harbor any of the investigated virulence genes. For the first time, Enterococcus isolates of three different species collected from diseased turkeys were investigated for their virulence properties in comparison. The results differed markedly between the Enterococcus species, with E. faecalis harboring the majority of investigated genes and virulence traits. However, the genotype did not entirely correlate with the phenotype or the isolates' virulence potential and pathogenicity for chicken embryos.